2016
DOI: 10.1080/00913847.2016.1176546
|View full text |Cite
|
Sign up to set email alerts
|

The role of inspiratory muscle training in the management of asthma and exercise-induced bronchoconstriction

Abstract: Asthma is a pathological condition comprising of a variety of symptoms which affect the ability to function in daily life. Due to the high prevalence of asthma and associated healthcare costs, it is important to identify low-cost alternatives to traditional pharmacotherapy. One of these low cost alternatives is the use of inspiratory muscle training (IMT), which is a technique aimed at increasing the strength and endurance of the diaphragm and accessory muscles of respiration. IMT typically consists of taking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 73 publications
2
54
0
3
Order By: Relevance
“…Flow-resistive loading typically involves a variable-diameter orifice that subjects must breathe through. The variable-diameter orifice in this type of device acts as a “leak” which increases the inspiratory pressure required to generate a given rate of airflow [101, 104]. Alternatively, pressure-threshold loading requires an individual to generate a predetermined amount of inspiratory pressure in order to open a one-way valve to enable airflow through the device [101, 104].…”
Section: Inspiratory Muscle Trainingmentioning
confidence: 99%
See 2 more Smart Citations
“…Flow-resistive loading typically involves a variable-diameter orifice that subjects must breathe through. The variable-diameter orifice in this type of device acts as a “leak” which increases the inspiratory pressure required to generate a given rate of airflow [101, 104]. Alternatively, pressure-threshold loading requires an individual to generate a predetermined amount of inspiratory pressure in order to open a one-way valve to enable airflow through the device [101, 104].…”
Section: Inspiratory Muscle Trainingmentioning
confidence: 99%
“…Both of these devices can be considered resistance loading devices. Separately, volume loading protocols such as normocapnic hyperpnea, have been employed, which require individuals to maintain a high ventilatory rate relative to their maximum voluntary ventilation [101, 104]. During this training, subjects engage in rebreathing to prevent hypocapnea from occurring.…”
Section: Inspiratory Muscle Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Airway inflammation, coupled with acute immunosuppression during periods of high training volume, may put athletes at risk for upper respiratory tract infection and related performance decrements (4, 7, 11, 26). The precise mechanism behind this airway inflammation is unclear (31). While it may not be due to bronchial hyper-reactivity, post-exercise respiratory symptoms (5, 13), or immune cell activation (5, 6, 24), it may be associated with elevated airway neutrophil counts (5, 6, 8, 24), as well as insufficient conditioning of inspired air and osmotic changes that damage the epithelium (3).…”
Section: Introductionmentioning
confidence: 99%
“…Inspiratory muscle training (IMT) has also been studied in relation to exertional dyspnoea [110]. A Cochrane review including five randomised controlled trials involving a total of 113 patients found that IMT improves respiratory muscle strength as measured by maximal mouth pressures (mean increase 13.34 cmH 2 O), but concluded that there was inadequate evidence to support or refute a role for IMT for asthma [111].…”
Section: Inhaled Corticosteroids and Dyspnoeamentioning
confidence: 99%